Pengaruh pendekatan Beyond Centers and Cierles Time (BCCT) dan Metode DRILL Terhadap Perkembangan Kognitif Anak di PAUD Mawar Kecamatan Nusaniwe Kota Ambon - Hermelina Abarua; Mirdayati Aihena; Alberthina Abetsi Haumahu; Lamberthus Johanes Lokollo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
Early childhood education is a crucial stage for stimulating cognitive development, thus requiring learning approaches suited to children’s characteristics. This study aims to examine the effects of the drill method, the Beyond Centers and Circle Time (BCCT) approach, and their combination on improving cognitive abilities of children aged 4–5 years at PAUD Mawar, Nusaniwe District, Ambon. The research employed a quantitative approach with an ex post facto design involving 50 children divided into two treatment groups. Data were collected through pretest and posttest based on cognitive indicators, then analyzed using t-test after fulfilling normality and homogeneity assumptions. Results indicated a significant difference between BCCT and drill groups, with BCCT yielding a higher mean score (75.00) compared to drill (67.11). These findings highlight that center-based learning is more effective in enhancing classification, symbol recognition, logical sequencing, and cause-effect reasoning than repetition strategies.